2003
DOI: 10.1093/oxfordjournals.rpd.a006341
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of the post-irradiation time from the glow curve of TLD-100

Abstract: The ratio of peak 3 to the sum of peaks 4 + 5 in TLD-100 was measured for various pre-irradiation and post-irradiation time periods, under conditions characteristic of routine personal dosimetry. It was confirmed that the value of this ratio depends only on the elapsed time between the prior readout and the present one, independent of the moment when the irradiation took place during the total time interval (storage time). This effect indicates that fading of peak 3 seems to be due mainly to changes in the uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Budzanowski et al (1999) demonstrated that by deconvoluting the MCP-N (LiF:Mg,Cu,P) glow curve it is possible to determine the time elapsed since exposure up to about 40 days using the peak 3/peak 4 and peak 2/peak 4 ratios. Weinstein et al (2003) draw similar conclusions, pointing out difficulties in using peak 2 in TLD-100 for this purpose. This feature is still not used in routine personal dosimetry but it could be applied in some special circumstances, e.g.…”
Section: Characteristics Under Test Minimal Measuring Rangesupporting
confidence: 62%
“…Budzanowski et al (1999) demonstrated that by deconvoluting the MCP-N (LiF:Mg,Cu,P) glow curve it is possible to determine the time elapsed since exposure up to about 40 days using the peak 3/peak 4 and peak 2/peak 4 ratios. Weinstein et al (2003) draw similar conclusions, pointing out difficulties in using peak 2 in TLD-100 for this purpose. This feature is still not used in routine personal dosimetry but it could be applied in some special circumstances, e.g.…”
Section: Characteristics Under Test Minimal Measuring Rangesupporting
confidence: 62%
“…When using the entire integrated glow curve, it should be noted that peaks 2 and 3 in LiF:Mg,Ti fade very quickly postirradiation, causing a much faster approach to the limits. This may be remedied by considering peaks 4 and 5 only, though this would cause problems with dosimetry applications requiring other peaks, such as the determination of post-irradiation fading time, which requires peak 2 [14]. In general, over a 90 day deployment period, a prompt dose of below 75 lGy caused crossover with the detection limit within 90 days, while a prompt dose of above 75 lGy did not cross the detection limit but did cross the determination limit within 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…If such a program is necessary for the desired dosimetry application, such as for determination of post-irradiation time in LiF:Mg,Ti, which requires the measurement of the areas of peaks 2, 3, 4, and 5 [14] and no other limit applies, some dosimetry applications may not be possible once the individual peaks in a glow curve are no longer separable by the computer.…”
Section: Theorymentioning
confidence: 99%
“…13 A potential drawback in the use of TLDs and Gafchromic film are that they demonstrate a strong temporal dependence in their measured signal after irradiation and thus require that the user wait for some amount of time for the signal to stabilize before measurements are recorded. 1,2,[14][15][16][17][18][19] Optically stimulated luminescent dosimeters (OSLDs) are another type of radiation detector that are widely used clinically for dose verification after the delivery of ionizing radiation in conventional dose rate (CONV) RT. Although the use of Al 2 O 3 :C OSLDs is fairly common in routine clinical practice, 20 their use and characterization in UHDR conditions has only been performed in a continuous radiation delivery proton FLASH pencil beamline with average dose rates ranging from 1 to 9000 Gy/s for OSLDs, with demonstrated dose-rate independence.…”
Section: Introductionmentioning
confidence: 99%